Comparison of MEMS-based photoacoustic microscopy in biomedical imaging - Pasin Suttikittipong; Parawee Tangkiatphaibun; Nicholas Piyawattanametha; Wibool Piyawattanametha (International Journal of Optomechatronics)
Photoacoustic microscopy (PAM) has emerged as a promising biomedical imaging technique, renowned for its capability to visualize the microvasculature and measure oxygen saturation levels in biological tissues, both non-invasively and in real-time. PAM combines the contrast benefits of optical imaging with the penetrating benefits of ultrasound. It offers high spatial resolution and deep tissue imaging, which is what microscopic and macroscopic imaging can’t do separately. This review presents fundamental knowledge of PAM’s theoretical model and the sensing mechanism. Using a Micro-Electro-Mechanical Systems or Microelectromechanical Systems (MEMS), various PAM optimizing techniques are covered, ranging from design, materials, and algorithms. Discussions also include opinions on future MEMS-based PAM technology development tendencies.